Peran Pondok Pesantren Dalam Membentuk Karakter Santri Di Pondok Pesantren Darus Sholihin - Novi Savita; Ruwaidah Ruwaidah; Fauzi Ahmad Syawaluddin; Rendi Fitra Yana (STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
This study aims to describe the role of Darus Sholihin Islamic Boarding School in Rantauprapat in shaping students’ character, the character-building patterns implemented, as well as the supporting and inhibiting factors involved. The study employed a qualitative approach using a field research design. Data were collected through interviews, observations, and documentation. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that Darus Sholihin Islamic Boarding School plays an important role in shaping students’ character through a boarding school education system, habituation of worship practices, the study of classical Islamic texts (kitab kuning), teacher role modeling, and various religious and extracurricular activities. The character-building process is carried out through methods of role modeling, habituation, training, advice, and the implementation of rewards and punishments. The character values developed include religiosity, discipline, responsibility, honesty, independence, and mutual respect. Supporting factors include a conducive boarding school environment and the active role of educators, while the inhibiting factors include external environmental influences, the diverse family backgrounds of the students, and limited supervision due to the large number of students.